Comparison between in vitro embryo production using Y-sorted sperm and timed artificial insemination with non-sorted sperm to produce crossbred calves - de Oliveira Bezerra, Alexandre; Nicacio, Alessandra Corallo; de Oliveira Menezes, Gilberto Romeiro; da Costa Gomes, Rodrigo; da Silva, Luiz Otavio Campos; de Souza Rocha-Frigoni, Nathália Alves [UNESP]; Mingoti, Gisele Zoccal [UNESP]; da Silva Leão, Beatriz Caetano [UNESP]; da Costa e Silva, Eliane Vianna; Nogueira, Ériklis (Elsevier, 2019)
Due to the increasing use of in vitro embryo production (IVEP) and the importance of crossbreeding for beef production, pregnancy rates of Nelore recipients were evaluated following Fixed Time Embryo Transfer with fresh or vitrified IVEP embryos produced with Y-sorted sperm of Angus bulls (B. taurus) or Fixed Time Artificial Insemination using non-sorted sperm. For IVEP in Experiment 1, oocytes were obtained using Ovum Pick Up (OPU) (n = 84 embryos) or from ovaries from a slaughterhouse (SLAUGHTER, n = 66 embryos). In Experiment 2, with oocytes obtained by OPU, IVEP embryos were fresh (FRESH, n = 271) or after vitrification/warming (VITRIFIED, n = 79) and PR was compared with FTAI (n = 239). In Experiment 1, cleavage rates were 63.8% and 39.1% for OPU and SLAUGHTER groups, respectively (P = 0.02), and blastocyst rates were 30.5% and 14.7%, respectively (P = 0.09). The PR was similar when considering the source of oocytes (OPU = 35.7%; SLAUGHTER = 25.8%; P = 0.17). In Experiment 2, there was no difference in PR for FRESH or VITRIFIED embryos (34.3% and 30.4%, respectively, P = 0.72), but lesser than FTAI (47.7, P = 0.002). It is concluded that the IVEP with Y-sorted sperm associated with vitrification or embryos produced with oocytes from different sources did not affect PR when there was transfer of crossbred embryos into recipients, and can optimize large-scale application of IVEP technology; however, FTAI pregnancy rates with non-sex sorted sperm were greater.
Keywords: Crossbreeding; Cryopreservation; FTAI; FTET; Nelore-Angus